Balancing Academic and Personal Life: Challenges for Medical Students - Fauziah, Rizqia Shafa; Hanami, Yuliana (Psyche 165 Journal, 2024)
Medical students are found to experience stress with a considerable impact because of the academic studies they are undertaking. High demands compared to non-medical students can interfere with other life domains, such as personal life. This interference can manifest in several ways, such as diminished time for social interactions and leisure activities. The purpose of this study was to explore and understand the potential impact on the relationship between academic life and personal life. The research was conducted with a sample of 7 medical student participants from Universitas Padjadjaran. Participants completed a questionnaire with 5 open-ended questions designed to capture their experiences and perspectives in detail. The findings revealed that a significant number of participants struggle with time management, feeling that their academic commitments leave them with minimal time for free activities and social engagements. This imbalance contributes to a sense of inadequacy in maintaining a fulfilling personal life. The study highlighted that a well-rounded personal life is crucial for sustaining optimal academic performance. A good personal life can provide good academic conditions, but the lack of free time for personal life makes participants do other alternatives such as postponing, procrastinating, and causing stress. Addressing these issues requires a holistic approach that not only alleviates academic burdens but also promotes a healthy balance between professional and personal domains. It’s essential for ensuring the well-being and success of medical students in both their academic pursuits and personal life.